2018
DOI: 10.29252/beat-060305
|View full text |Cite
|
Sign up to set email alerts
|

Massive Blood Transfusions and Outcomes in Trauma Patients; An Intention to Treat Analysis

Abstract: Objective:To determine if there exists an upper limit for amount of blood transfused in trauma patients before it reaches a point of futility. Methods:A prospective cohort study was conducted on 131 patients who received massive blood transfusion (MBT), defined as 10 U or higher of PRBCs received in the initial 24 hours. Data collected from a Level II trauma center registry were used to analyze reports of adult patients from July 2014 to 2017. Cohorts were divided by amount of blood received - 0 to 9 U, 10-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…Most research has focused on determining a transfusion threshold, based on the number of RBC units transfused, above which mortality increases significantly. 6,16,[27][28][29][30] Our study is unique in terms of demonstrating the predictive value of nadir pH, peak lactate, and age on in-hospital mortality among massively transfused patients across a broad range of surgical departments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most research has focused on determining a transfusion threshold, based on the number of RBC units transfused, above which mortality increases significantly. 6,16,[27][28][29][30] Our study is unique in terms of demonstrating the predictive value of nadir pH, peak lactate, and age on in-hospital mortality among massively transfused patients across a broad range of surgical departments.…”
Section: Discussionmentioning
confidence: 97%
“…With respect to massive transfusions, we are unaware of any studies to date that have analyzed futility in the context of certain laboratory thresholds for pH and lactate. Most research has focused on determining a transfusion threshold, based on the number of RBC units transfused, above which mortality increases significantly 6,16,27–30 . Our study is unique in terms of demonstrating the predictive value of nadir pH, peak lactate, and age on in‐hospital mortality among massively transfused patients across a broad range of surgical departments.…”
Section: Discussionmentioning
confidence: 97%
“…6,7,27,30,33 Lo et al 7 recommended developing a futility index to predict when death may be unavoidable in spite of large volume blood administration, to aid physicians in medical decision-making during UMT in trauma. Liu et al 38 examined the mortality rates in trauma patients receiving MT (>10 units RBC/24 hours), and although the study was limited by its small sample size (n = 131), the authors suggested that 40 units RBC may be a potential cutoff value at which patient survival begins to decrease dramatically.…”
Section: Author Yearmentioning
confidence: 99%
“…A 2018 study of outcomes versus amount of blood transfused at one trauma center concluded that 40 units of packed red blood cells may constitute a threshold at which survival rates begin to decrease and futility can be considered [4]. A 1998 report on the upper limit to massive blood transfusion after severe trauma, however, had concluded that discontinuation of short-term care cannot be justified at less than 68 units [5].…”
Section: Introductionmentioning
confidence: 99%